Linking human wellbeing and urban greenspaces: Applying the SoftGIS tool for analyzing human wellbeing interaction in Helsinki, Finland - leBrasseur, Richard (Frontiers in Environmental Science, 2022)
This paper reviews a study into the relationships between greenspaces and the benefits to psychological, social, and physical aspects of human wellbeing achieved through interaction in the Helsinki Urban Region in Finland. This relationship is theorized, analyzed, and measured through the transactional paradigm of Affordance Theory and is operationalized through the use of a public participation geographic information system (PPGIS) questionnaire, SoftGIS, which activated the urban greenspace-human wellbeing interaction through its map-based data collection. Over 1800 unique place-based relationships were statistically analyzed. Findings revealed that Helsinki’s greenspaces provided, overall, mostly physical and social wellbeing benefits; the psychological benefits such as reduction of stress and mental relaxation were not as frequent in these urban greenspace interactions. Results indicate multiple aspects of human wellbeing are supported by interaction with urban greenspaces of varying characteristics within the region but the urban greenspaces which provided the most human wellbeing benefits included large size, woodland typology, moderately maintained with loose or ‘wild’ vegetation, and few amenities such as benches and structures. The study’s implications include urban planning, public policy, and human health as well as insight into the multifunctional design and strategic management of greenspaces in urbanizing regions to provide continued and improved ecosystem services and benefits to humans and nature.